Tendon lengthening and fascia release for healing and preventing diabetic foot ulcers: a systematic review and meta‐analysis - Sarah M. Dallimore; Michelle R. Kaminski (Journal of Foot and Ankle Research, 2015)
Abstract Background Diabetic foot ulcers have a devastating impact on an individual's health‐related quality of life and functional status. Additionally, diabetic foot ulcers impose a significant economic burden on our health care systems as a result of complications such as infection, hospitalisation and amputation. The current gold standard treatment for diabetic foot ulcers is total contact casting. However, the rate of ulcer recurrence is high, indicating the need for more effective long‐term treatment options. Therefore, the aim of this study was to systematically identify, critique and evaluate all literature investigating the effectiveness of Achilles tendon lengthening, gastrocnemius recession and selective plantar fascia release in healing and preventing diabetic foot ulcers. Review Searches were conducted in MEDLINE, CINAHL, AMED, EMBASE and The Cochrane Library from the earliest available date to November 2014. Methodological quality of included studies was assessed using the Downs and Black checklist. Data from randomised‐controlled trials were analysed using random effects meta‐analysis. For all other studies, data were analysed descriptively. Eleven studies (614 participants) were included in the review, with a median sample size of 29 participants. Meta‐analysis of two randomised‐controlled trials found that there was no statistically significant difference between Achilles tendon lengthening or gastrocnemius recession and total contact casting for time to healing of diabetic foot ulcers (mean difference, MD, 8.22 days; 95 % CI, −18.99 to 35.43; P = 0.55; I2 = 34 %) and the rate of ulcers healed (risk ratio, RR, 1.06; 95 % CI, 0.94 to 1.20; P = 0.34; I2 = 41 %). The rate of ulcer recurrence was significantly lower following Achilles tendon lengthening or gastrocnemius recession than total contact casting (RR, 0.45; 95 % CI, 0.28 to 0.72; P < 0.001; I2 = 0 %). Conclusions Achilles tendon lengthening and gastrocnemius recession appear to be effective surgical treatments for healing diabetic foot ulcers. The rate of ulcer recurrence was lower following Achilles tendon lengthening or gastrocnemius recession procedures compared to total contact casting treatment alone. Therefore, these surgical procedures may provide viable treatment options for the management and prevention of diabetic foot ulcers. Further rigorous randomised‐controlled trials with longer follow‐up are required to determine the long‐term effectiveness and safety of these procedures.